Periodontitis induces endothelial dysfunction in mice - Maria Parvaneh; Paul K. Witting; Jaqueline Ku; Tala Moradi; Elif Eroglu; Ben Freedman; Greg T. Sutherland; Andrew McCorkindale; Boris Guennewig; Phannaphat Choowong; Kim Bell-Anderson; Gregory Cooney; et al. (Scientific Reports, 2021)
Abstract The treatment of periodontitis has numerous positive effects on established chronic health conditions, including cardiovascular disease and diabetes. However, ethical considerations do limit the establishment of human trials to investigate whether periodontitis promotes the early stages of chronic conditions. Therefore, the aim of this study was to investigate whether periodontitis induces endothelial dysfunction in hyperlipidemic apolipoprotein E gene-deficient (ApoE-/-) mice. Forty-five 8-week-old ApoE-/- mice were challenged by oral lavage with Porphyromonas gingivalis and Streptococcus gordonii for 4 weeks. A subgroup of animals (n = 15–17/group) was placed in a metabolic chamber immediately before euthanasia at 4 weeks to measure VO2/CO2 concentrations and voluntary locomotion. In infected and control animals alveolar bone levels were measured by x-ray imaging and endothelial function was determined by measuring endothelial-dependent vasorelaxation of aortic rings. The mRNA expression levels of serum amyloid A and tumor necrosis factor were determined in liver tissues by qRT PCR and protein concentrations in serum by ELISA. Caecal contents were analysed by sequencing to determine changes to the gut microbiota to investigate linkages between microbiome and systemic changes. The results showed that oral lavage of P. gingivalis and S. gordonii for 4 weeks, initiated periodontitis in ApoE-/- mice, similar to the human situation. The oral inflammation was accompanied by a significant increase in mRNA expression of pro-inflammatory mediators serum amyloid A1 and tumor necrosis factor in the liver. Mice with periodontitis also exhibited impaired endothelial-dependent vasorelaxation responses to acetylcholine. This systemic response was connected to increased energy expenditure, locomotion and respiratory quotient. No differences were detected in caecal microbiota between the infected and control animals. Overall, this is the first report that provide evidence that periodontitis induces endothelial dysfunction in mice. Other systemic responses observed in response to the local reaction need further investigation. The study suggests that early prevention of periodontitis may help limit the early stages of endothelial dysfunction that is linked to atherogenesis in humans.